VARIATION IN INTERNAL CAROTID ARTERY PROTRUSION AND DEHISCENCE IN A SUBSET OF KARACHI POPULATION - Lakhani, Mubina; Raza, Iffat; Mohiuddin, Maria; Khan, Rosheena Nabeel; Sidhwani, Santosh Kumar; Hassan, Nuzhat (Journal of Rawalpindi Medical College, 2023)
Objective: To find out the frequency of protrusion of Internal Carotid artery in sphenoid sinus and dehiscence of carotid canal in a subset of Karachi population. Study design: This was a Cross-sectional study conducted at Radiology department of Ziauddin university. Methodology: We analyzed 270 head and neck CT scans 270 Head and neck CT scans (540 sides) were analyzed. CT was performed on a 16 slice Toshiba Alexion at Ziauddin Hospital, Karachi —removed for blind review—. SPSS version 20 was used for data analysis. Results: Out of 270 CT scans analyzed, 28 (10.3) scans showed protrusion of ICA in sphenoid sinus. Out of 45 (16.6) of the subjects showed dehiscence of carotid canal. Out of total dehiscence present unilateral cases were more frequent as compared to bilateral. Unilateral protrusion was also more common as compared to bilateral protrusion of ICA. Conclusion: Knowledge of dehiscence and protrusion related to ICA and sphenoid sinus anatomy is essential to avoid complications in endoscopic sinus surgery.